ANALISIS DEL CUMPLIMIENTO TRIBUTARIO EN LA EMPRESA COMERCIAL FISA MADERATO EN LA CIUDAD DE LOJA, PERIODO 2017” - Encalada Cacay, Sandy María (2020)
The thesis work entitled "ANALYSIS OF TAX COMPLIANCE IN THE FISA MADERATO COMMERCIAL ENTERPRISE IN THE CITY OF LOJA, PERIOD 2017" was carried out with the purpose of demonstrating the degree of compliance with the tax and tax obligations of the company, compliance with current regulations, work that was developed in compliance with the previous requirement to choose the degree of Accounting Engineering and Auditing Public Accountant - Auditor, Accounting and Audit, Legal, Social and Administrative Faculty of the National University of Loja . The work was developed planning each of the phases, being necessary for its correct execution, using methods that helped the collection of necessary information, facilitating the study of laws, regulations, provisions and theoretical references that allowed the fulfillment of the general objective, as well The specific objectives set forth were satisfactorily fulfilled since the identification of the tax regulations of the company was made based on what is determined by the Constitution of the Republic of Ecuador and mainly the Organic Law of the Internal Tax Regime (LORTI), laws, regulations and resolutions to subsequently make the comparison of the values of reports in books vs values declared by VAT declaration concepts, withholding tax declarations, dependency relationship annex and simplified transactional 10 annex, to determine if the company fulfills its obligations of according to what ue establishes the regulations and with this a report of the analysis of the Tax Compliance of the Commercial Company FISA MADERATO was prepared, where the result obtained itself was recorded, which contains objectives, scope and general conclusions of the analysis carried out, which contributes to providing corrective measures for its improvement in tax compliance. Finally, the above-described process allowed obtaining reliable, timely and truthful information from the analysis applied to the company. Among the results, the lack of an adequate control of the company's records that affect the moment of reflecting the true values in the statements is highlighted. received by the SRI.